Resveratrol-derived MDM2 inhibitors: Synthesis, characterization, and biological evaluation against MDM2 and HCT-116 cells - Oraibi Amjad Ibrahim; Dawood Ashour H.; Debbabi Nawres; Almukram Ali Majeed Ali; Almaary Khalid S.; Dabiellil Fakhreldeen; Chekir-Ghedira Leila; Kilani-Jaziri Soumaya (Open Chemistry, 2025)
This study investigates the biological potential of novel resveratrol-based derivatives targeting the MDM2 protein, a critical regulator of the tumour suppressor p53 in cancer therapy. We synthesized and characterized four derivatives of (E)-2,4-dimethoxy-6-(4-methoxystyryl) benzaldehyde using mass spectrometry, proton nuclear magnetic resonance, and Fourier-transform infrared spectroscopy. These derivatives were specifically designed to enhance binding affinity, stability, and selectivity compared to inhibitors like Nutlin. Biological evaluation through MTT assays revealed varying antiproliferative activities against HCT-116 cancer cells. AMJ3 exhibited the strongest activity, with an IC50 value of 22.69 ± 2.47 µg/mL, outperforming that of the reference compound Nutlin (IC50: 62.72 ± 3.15 µg/mL). MDM2-p53 inhibitory activity confirmed AMJ3 as the most potent inhibitor (IC50: 0.24 ± 0.02 µM), followed by AMJ5 (IC50: 0.48 ± 0.04 µM), both surpassing Nutlin (IC50: 0.39 ± 0.03 µM). Molecular docking studies for AMJ3 and AMJ6 achieved superior glide scores of −5.6 and −4.9, respectively. Molecular dynamics simulations validated these findings, showing that AMJ3 formed a stable hydrogen bonding interaction with Leu33 of the MDM2 protein and hydrophobic interactions with Ile40 and Tyr79, while Nutlin-3a showed weaker interactions overall. These results highlight AMJ3 and AMJ5 as promising MDM2 inhibitors with enhanced specificity and efficacy and better activity than Nutlin.